In-situ TEM investigation of failure processes in metal-plastic joint interfaces. (September 2022) - Horiuchi, Shin; Liu, Yida; Shigemoto, Yuri; Hanada, Takeshi; Shimamoto, Kazumasa
Abstract: The nano-scale failure behaviors of joint interfaces were investigated by in-situ straining technique to observe the crack propagations in a transmission electron microscope (TEM). The thin sections of bonded interfaces were subjected to tensile loading by using a specially designed specimen holder. The deformation at the crack tip before the initiation of crack and the initiation of the crack were observed in the nanometer level. The experiments with identical and dissimilar polymer/polymer welded specimens allowed us to see the plastic deformation ahead of the crack tip and the creation of craze, which is the typical failure mode of polymers. The failure of the interfaces between aluminum alloy (Al5052) and epoxy adhesive and between Al5052 and thermoplastic directly bonded by injection molding were investigated to visualize the failure behaviors in small scale before the macroscopic fracture of the interfaces. The in-situ straining technique under a high-resolution scanning transmission electron microscopy (STEM) mode enables the observation of micro deformation ahead of the crack, microvoids produced prior to the crack progression and the failure of the surface modified layer on Al surface.